2012
DOI: 10.1161/atvbaha.111.235358
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Specific Scavenger Receptor Class AI Binding Peptide for Targeting the Inflammatory Atherosclerotic Plaque

Abstract: Objective-Scavenger receptor A (SR-A) is abundantly expressed by macrophage and plays a critical role in foam cell formation and atherogenesis. In search of selective SR-AI antagonists, we have used affinity selection of a phage displayed peptide library on the synthetic extracellular domain of SR-AI. Methods and Results-Phage selection led to an almost 1,000-fold enrichment of SR-AI binding phage, which bound avidly to human THP-1 cells. A 15-mer corresponding to the peptide insert of the major SR-AI binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…12,27,28 Recently, our group successfully identified a small 16-mer peptide (PP1) with high specificity and affinity for SR-AI, a promising homing device for contrast agents. 19 Concordant with our previous study, PP1-conjugated USPIO was preferentially taken up by macrophages and VSMCs. Phagocytosis occurred in an SR-dependent manner because SR-AI inhibitor (fucoidan and dG 16 ) coincubation blunted the incremental uptake, which was not observed by a partial SR-AI inhibitor (dG 3 T 13 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…12,27,28 Recently, our group successfully identified a small 16-mer peptide (PP1) with high specificity and affinity for SR-AI, a promising homing device for contrast agents. 19 Concordant with our previous study, PP1-conjugated USPIO was preferentially taken up by macrophages and VSMCs. Phagocytosis occurred in an SR-dependent manner because SR-AI inhibitor (fucoidan and dG 16 ) coincubation blunted the incremental uptake, which was not observed by a partial SR-AI inhibitor (dG 3 T 13 ).…”
Section: Discussionsupporting
confidence: 91%
“…19 To address its potential for human plaque imaging, we generated LDLr −/− chimeras with hematopoietic human SR-AI expression by bone marrow transplantation (>90% bone marrow reconstitution after 6 weeks). Chimeras with hematopoietic SR-AI deficiency (SR-AI −/− ) and wild-type bone marrowtransplanted LDLr −/− mice served as control.…”
Section: Segers Et Al Sr-ai-targeted Molecular Imaging Of Atherosclermentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to activated macrophages, folate binds to receptors on normal epithelial cells and tumor cells (13). Segers et al (14) reported a peptide that binds the scavenger receptor-A on macrophages found within atherosclerotic plaques, but scavenger receptor-A is also expressed on all dendritic cells.…”
mentioning
confidence: 99%